Long-term clinical activity, safety and patient-reported quality of life for emactuzumab-treated patients with diffuse-type tenosynovial giant-cell tumour. (December 2020) - Cassier, Philippe A.; Italiano, Antoine; Gomez-Roca, Carlos; Le Tourneau, Christophe; Toulmonde, Maud; D'Angelo, Sandra P.; Weber, Kristy; Loirat, Delphine; Jacob, Wolfgang; Jegg, Anna-Maria; Michielin, Francesca; Christen, Randolph; et al.
Abstract: Objectives: This study investigated the safety, clinical activity and patient-reported outcomes of patients with diffuse-type tenosynovial giant-cell tumour (dTGCT) of the soft tissue who were treated with emactuzumab, a humanised anti-colony stimulating factor 1 receptor (CSF1R) monoclonal antibody and were followed up for up to 2 years after the start of treatment. Methods: In this open-label phase 1 study (ClinicalTrials.gov NCT01494688 ), patients received intravenous (IV) emactuzumab from 900 to 2000 mg every two weeks in the dose-escalation phase and at the optimal biological dose of 1000 mg with different schedules in the dose-expansion phase. Adverse event (AE) rates and biomarker assessments from tumour biopsies were analysed. Quality of life was assessed using a standard questionnaire (EuroQol-5D-3L) and the WOMAC® 3.1 Osteoarthritis Index. Tumour responses were determined with magnetic resonance imaging. Results: Altogether, 63 patients were enrolled into the study. The most frequently reported AEs were pruritus, asthenia and oedema. In 36 patients for whom biopsy tissue was available a substantial decrease of CSF1R-positive and CD68/CD163-positive macrophages was detected. The independently reviewed best overall objective response rate (ORR) (Response Evaluation Criteria in Solid Tumors version 1.1) was 71%. Responses were durable, and an ORR of 70% and 64% was determined after one or two years after enrolment into the study. Clinical activity was accompanied by an improvement in EuroQol-5D-3L and particularly the joint disorder–specific WOMAC score. Conclusions: Systemic therapy of dTGCT patients with emactuzumab resulted in pronounced and durable responses associated with symptomatic improvement and a manageable safety profile. Highlights: This phase I study of 63 diffuse-type tenosynovial giant-cell tumour patients indicated an objective response rate of 71%. Objective responses were durable and assessable after 1 or 2 years after enrolment. The safety profile was manageable. Quality of life including joint disorder–specific Western Ontario and McMaster Universities Osteoarthritis Index score indicated improvement.